Streamlining Education Institution Through Waqf Enlargement: An Experience of Gontor System - Bahroni, Imam (AT TADIB, 2012)
Education is a process through which a person could actualize himselfto be powerful individual and part of community. Powerful because he couldnot only live in the society but develop the community, he is also ready to leadand ready to be led and make the people dynamic. A person in this instance,who wishes to actualize his potencies, needs various trainings, positive and rightmovements for physics, mind and heart. First, when the physical movementcontinuously carried out in this life, he becomes physically strong and healthy.That is why a person needs sport, good food, and enough resting. Second, themind also needs to be trained through various movements in the form of hardthinking on a positive and qualitative thing where the strong knowledge lays.Third, in order to strengthen his heart a person needs spiritual movement. Thismovement is naturally done through worship, pray and remembrance of Allah,fasting and night prayer. When these three kinds of movements practiced in lifeit becomes strength for the human being as an individual and part of the groupof people in the society.